Effects of dissolved mercury on embryogenesis, survival, growth and metamorphosis of Crassostrea gigas oyster larvae - Beiras, Ricardo; His, Edouard (Marine Ecology Progress Series, 1994)
The effects of mercury (Hg) concentrations ranging from 0 (control) to 1024 µg 1-1 upon embryogenesis, survival, growth and metamorphosis of Crassostrea gigas (Thunberg) oyster larvae were investigated. Embryogenesis was abnormal in 50 % of the individuals at 11 µg 1-1 . The 48 h LD50 for D·shaped, umbonate and pediveliger larvae were 33, 115 and 200 µg 1-1 respectively. The increase in LD50 was partially explained by the larval weight increase, although weight-specific tolerance to Hg was higher in smaller larvae. Growth, the most sensitive physiological process studied, was significantly retarded at 4 µg 1-1. The metamorphosis rate was significantly reduced when competent pediveligers were exposed to 64 µg 1-1 for 48 h prior to the addition of the metamorphosis inducer epinephrine. The implications of the present results for monitoring pollution by utilising different bivalve larval stages are discussed.